Extensive late skin lesion due to fluoroscopy ionizing radiation exposure: a case report - Iarley Peron Faria; Thaís Gomes Casali; Marcelo Torres De-Souza; Larissa Freesz de Almeida (Revista Brasileira de Cirurgia Plástica, 2021)
The radiation-induced skin reaction (RCIR) is usually characterized by edema, hyperemia, fibrosis, ulceration, pain and itching on the skin. It is known that radiation disrupts the normal process of cell division and regeneration, resulting in damage that may involve impairment in the function of endothelial cells, inflammation and even cell death. The recovery of tissue damage by radiation depends on multiple factors related to the procedure performed and intrinsic to the patient. We present an atypical case of RCIR, whose lesions presented very unpredictable behavior and difficult clinical management. In addition, it is emphasized the importance of surgical intervention in this case, fundamental for the patient's proper treatment.